Hadirnya Kemasan Syariah dalam Bisnis Perhotelan di Tanah Air - Anwar Basalamah (Bina Nusantara University, 2011)
Lately, the business development based on religion background, Islam, is growing and expanding. Besides banking, insurance, education, and others, the sharia concept also in hotel. Sharia hotel is an interesting phenomenon. On the other side, the appearance of sharia hotels in the nation is having two thumbs up. Sharia hotel brand, as in other sharia products, eventhough the target market is more specific and segmented, but it is possible that the product will have high demand not from Islamic community only. The article uses research method regarding trend analysis and literature review. The result showed that there is challenge towards sharia hotels to present concept, human resources and implementation that represents business figure based on sharia: eastern specialty, barokah, classy, and interesting.